심각한 판막질환이 없는 심방세동 환자에서 RR 간격과 초기 확장기 승모판윤 속도와의 상관관계 - 최여원; 김정은; 조은정; 김은영; 서기우; 이경헌; 이광제; 김상욱; 김태호; 고홍숙; 김치정; 류왕성 (Korean circulation journal, 2008)
Background and Objectives: Irregular RR intervals in atrial fibrillation (AF) results in beat to beat changes in hemodynamical parameters. Early diastolic mitral annulus velocity (E’) is one of the parameters that represent diastolic function of the left ventricle (LV). In this study, we have investigated the effects of continuous changes of systolic functions in AF on the diastolic functions of the LV. Subjects and Methods: E’ (35-40 beats) was recorded in 31 AF patients that did not have significant valvular heart diseases. The relationships between preceding RR intervals (RR-1) or pre-preceding RR intervals (RR-2) and E’s were obtained using a logarithmic function. Results: Slopes between RR-1 and E’ varied from -1.62 to 1.04 in total coordinates. In the logistic regression analysis patients with negative slopes were found to have a larger left atrial size than patients with positive slopes (5.5±0.67 cm vs. 4.9±0.56 cm, p=0.02). Slopes were negatively related with mean RR intervals in the Pearson correlation analysis (r=-0.40, p=0.028). Slopes between RR-2 and E’ were also variable and were not associated with other parameters. Conclusion: Beat to beat changes in systolic functions derived from irregular RR intervals in AF had variable effects on diastolic functions among patients. The relationship between RR-1 and E’ was associated with LA sizes and mean RR intervals. KCI Citation Count: 1